2021
DOI: 10.3390/cancers13061284
|View full text |Cite
|
Sign up to set email alerts
|

Pain Progression at Initiation of Cabazitaxel in Metastatic Castration-Resistant Prostate Cancer (mCRPC): A Post Hoc Analysis of the PROSELICA Study

Abstract: Background: In the PROSELICA phase III trial (NCT01308580), cabazitaxel 20 mg/m2 (CABA20) was non-inferior to cabazitaxel 25 mg/m2 (CABA25) in mCRPC patients previously treated with docetaxel (DOC). The present post hoc analysis evaluates how the type of progression at randomization affected outcomes. Methods: Progression type at randomization was defined as follows: PSA progression only (PSA-p; no radiological progression (RADIO-p), no pain), RADIO-p (±PSA-p, no pain), or pain progression (PAIN-p, ±PSA-p, ±RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Despite medication development in the past decade, mCRPC remains deadly with limited therapeutic options [ 5 , 6 ]. The majority of approved anticancer drugs for PC, including enzalutamide, abiraterone/prednisone, docetaxel, and cabazitaxel, do not have a durable impact in the setting of established metastatic liver disease due to acquired therapeutic resistance [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite medication development in the past decade, mCRPC remains deadly with limited therapeutic options [ 5 , 6 ]. The majority of approved anticancer drugs for PC, including enzalutamide, abiraterone/prednisone, docetaxel, and cabazitaxel, do not have a durable impact in the setting of established metastatic liver disease due to acquired therapeutic resistance [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life was also reported to be better in the radium‐223 group compared to placebo in ALSYMPCA trial. 15 Interestingly, a recent post hoc analysis of the phase III Proselica trial 28 analyzed pain progression at the initiation of cabazitaxel treatment and found that the pain progression was associated with aggressive disease and shorter survival time compared to the radiological or PSA progression (12.0 vs. 16.8 vs. 18.4 months, respectively, p < 0.001). Pain response could be a potential indicator of the clinical benefit from radium‐223 and a marker of the aggressive course of mCRPC.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[7][8][9][10] Not losing the window of opportunity, especially in patients with poor prognostic features, is of great importance. 11,12 In the study of Annala et al 85 patients were eligible for crossover but only 55 patients (58%) actually received the alternative treatment, mostly due to frailty after the previous treatment. 6 In the CARD study, 22% of patients who progressed in the ARPI arm subsequently received palliative radiotherapy and 36% received no subsequent therapy at all, suggesting >50% of those who progressed may have missed the window of opportunity for receiving the more effective treatment.…”
mentioning
confidence: 99%